Aerodynamic analysis of vertical axis wind turbine - Saat, Abdullah Fauzi; Rosly, Nurhayati (FAZ Publishing, 2019)
Wind turbine is a device that converts wind energy into electrical energy because wind is a type of renewable energy. There are many types of vertical wind turbine in the modern era, the type of wind turbine chosen for this thesis is called Darrieus type wind turbine. This specific type of wind turbine is patented by a French aeronautical engineer named Georges Jean Marie Darrieus. The goal of this study is to understand the aerodynamic characteristic of Darrieus wind turbine focusing on power coefficient. Besides that, suggestion of an improved design of this particular Darrieus wind turbine ia also included. The software used to initiate a list of rotor power coefficient (Cp) is FORTRAN 77. By calculating the Cp with range values of tip speed ratios (TSR) of Darrieus wind turbine theoretically, we can observe the reference trend or curve of the Cp versus TSR graph for better illustration of turbine characteristic. Furthermore, simulation analysis is done by using the software named ANSYS Fluent to study the Cp values of the turbine as Computational Fluid Dynamics (CFD) Simulation. A 3D design of Darrieus wind turbine was developed in order to run the CFD simulation in ANSYS. Once the simulation is done, the torque values are extracted to calculate the power produced by the 3D turbine model. Thus, the Cp can be calculated. Finally an improved design is proposed in order to compare and validate the improvement in term of power produced. By increasing the number of blades, a significant different in results can be obtained.